Aristotle's Philosophical Thought Now and Then: With Emphasis on His Ontology and Teleology - Rousidi, Konstantina (Conatus - Journal of Philosophy, 2018)
This paper seeks to discuss extensively the context of Aristotelian metaphysics and ontology, as well as the way in which the latter have contributed to relevant thought and science today. In addition, through an in-depth analysis in the above area, a smooth transition will be made to Aristotelian teleology, its analysis and explanation, as well as how it is conceived or encountered today. In particular, the discussion will begin with the necessary historical background and biographical reference in the context of Aristotle's education and action. The range of cultures it influenced, the sciences it dealt with and the principles it proposed will be presented. At this point the necessary familiarity with Aristotelian "biology", physiology and logic will be achieved in order to successfully analyze the first part of the research. Subsequently, the emphasis on Aristotelian teleology, namely the second part of the work, will extend the discussion to the fields of psychology, seeking, at the end, an experimental comparison with some aspects of the psychoanalytic principle of pleasure. Finally, the work, while maintaining the necessary scientific impartiality but also critical view of the data, presenting theories not only of Aristotelian supporters but also critics, seeks to provide an additional reading of Aristotelian universal materialism by productively enriching the context of the subject in question. reflection.